Synthesis of gold nanoparticles stabilized by a pyrazinium thioacetate ligand: A new colorimetric nanosensor for detection of heavy metal Pd(II) - Anwar, Ayaz; Minhaz, Aaliya; Khan, Naveed Ahmed; Kalantari, Katayoon; Afifi, Amalina Muhammad; Shah, Muhammad Raza (Elsevier, 2018)
We developed a facile method for the synthesis of Gold nanoparticles (AuNPs) stabilized by cationic 1-(3-(acetylthio)propyl)pyrazin-1-ium ligand denoted as APP. Gold nanoparticles stabilized by APP (APP-AuNPs) are found to be polydispersed in size and lie in the range of 5–10 nm. We report a robust and sensitive protocol for the detection of heavy toxic metal ion Pd(II) in water using APP-AuNPs. From the fifteen salts tested, APP-AuNPs demonstrated a sensitive and selective spectrophotometric signal, as well as naked eye indication for recognition of Pd(II) ions. Pd(II) ions caused a colorimetric, distinguished response to APP-AuNPs based on the aggregation induced decrease of surface plasmon resonance (SPR) band. The nanosensor probe displayed a sensitive response to the Pd(II) ions in a wide range of concentration and pH, with detection limit of as low as 4.23 μM. Furthermore, the decrease in SPR band of APP-AuNPs due to Pd(II) ions was unaffected by tap water samples and/or human blood plasma.